Mitochondrial oxidant stress promotes α-synuclein aggregation and spreading in mice with mutated glucocerebrosidase - Pietro La Vitola; Eva M. Szegö; Rita Pinto-Costa; Angela Rollar; Eugenia Harbachova; Anthony HV Schapira; Ayse Ulusoy; Donato A. Di Monte (npj Parkinson's Disease)
Abstract In this study, heterozygous expression of a common Parkinson-associated GBA1 variant, the L444P mutation, was found to exacerbate α-synuclein aggregation and spreading in a mouse model of Parkinson-like pathology targeting neurons of the medullary vagal system. These neurons were also shown to become more vulnerable to oxidative and nitrative stress after L444P expression. The latter paralleled neuronal formation of reactive oxygen species and led to a pronounced accumulation of nitrated α-synuclein. A causal relationship linked mutation-induced oxidative/nitrative stress to enhanced α-synuclein aggregation and spreading that could indeed be rescued by neuronal overexpression of mitochondrial superoxide dismutase 2. Further evidence supported a key involvement of mitochondria as sources of reactive oxygen species as well as targets of oxidative and nitrative damage within L444P-expressing neurons. These findings support the conclusion that enhanced vulnerability to mitochondrial oxidative stress should be considered an important mechanism predisposing to pathology conversion in carriers of GBA1 mutations.